2022
DOI: 10.1590/fst.30221
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hygienic handling of food by consumers in the COVID-19 pandemic context: A cross-sectional study in Vietnam

Abstract: The objectives of this research are trifold. The first is to unveil antecedents of food-handling behaviors in the context of the COVID-19 pandemic. The second is to investigate the consistency of impacts of proposed determinants across different handling behaviors. The third is to confirm whether or not the premise of intention as the sole direct determinant of behavior in the Theory of Planned Behavior (TPB) holds. As such, TPB served as the guiding theory, and Factor Analysis and Seemingly Unrelated Regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, altering the habit of shopping for conventional fisheries food for organic ones remain a challenging quest. Old habits are ordinarily burdensome to convert but it may be more advantageous to try and encourage the formation of new favorable habits to obtain the desired behavior (Bell & Ulhas, 2020;Dang & Dam, 2022;Dang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, altering the habit of shopping for conventional fisheries food for organic ones remain a challenging quest. Old habits are ordinarily burdensome to convert but it may be more advantageous to try and encourage the formation of new favorable habits to obtain the desired behavior (Bell & Ulhas, 2020;Dang & Dam, 2022;Dang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these rationales, this study postulates that: H6: Intention significantly and positively influences OFF consumption behavior Perceived risk has been a pivotal concept in a spectrum of sustainable food studies worldwide, (Pandey et al, 2020;Wang & Tsai, 2014). Perceived risk is an expectation of a probably potential loss and plays a prime role in determining an individual's intention and is likely to negatively influence attitudes toward a behavior (Chen, 2017;Dang & Dam, 2022). In the consumption context, Hussain et al (2017) defined perceived risk as a subjective perception regarding the uncertainty and negative consequences of the purchase of a product, and Wu et al (2011) reported that in these situations, consumers often decreased purchase intentions.…”
Section: Literature Review and Empirical Frameworkmentioning
confidence: 99%
“…The most common clinical manifestation of COVID-19 is fever, but food handlers' awareness of food risks needs to be notified alongside any updates regarding the COVID-19. So, the diagnosis and treatment should be joined with the epidemiological data and CT imaging findings to prevent misdiagnosis (Gao et al, 2021;Dang & Dam, 2021) MDT breaks the barriers between disciplines, effectively promotes the construction of disciplines, realizes the joint improvement of doctors, departments and hospitals (Liu et al, 2007;Nikolovski et al, 2017;Slavova-Azmanova et al, 2015;Nazim, 2018). Therefore, we aimed to explore the effect of MDT mode in the diagnosis and treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%